Occupational infection and needle stick injury among clinical laboratory workers in Al-Madinah city, Saudi Arabia - Khabour, Omar F. (J Occup Med Toxicol, 2018)
BACKGROUND: Clinical laboratory workers face biohazard such as needlestick injury and occupational infection on a daily basis. In this study, we examined self-reported frequency of occupational infection and needlestick injury among the clinical laboratory workers in Al- Madinah, Saudi Arabia. METHODS: A total of 234 clinical laboratory workers were recruited from private and government health sectors to answer a self-administered questionnaire that was prepared to achieve the aims of the study. RESULTS: The results showed that approximately 33% of the sample had an experienced occupational infection while 24% had experienced a needlestick injury. Approximately, 49% reported that they always recap needle after use, whereas 15% reported doing that most of the times. Occupational infection, needlestick injury and recapping needles after use were associated with lack of training on biosafety (P < 0.05). CONCLUSION: The frequency of occupational infection and needlestick injury among clinical laboratory workers in Al-Madinah is high. Interventions related to biosafety and infection control and the use of needlestick prevention devices might be useful in lowering such frequency.